2015
DOI: 10.1364/oe.23.009109
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of focused short pulses through a multimode fiber

Abstract: Light propagation through multimode fibers suffers from spatial distortions that lead to a scrambled intensity profile. In previous work, the correction of such distortions using various wavefront control methods has been demonstrated in the continuous wave case. However, in the ultra-fast pulse regime, modal dispersion temporally broadens a pulse after propagation. Here, we present a method that compensates for spatial distortions and mitigates temporal broadening due to modal dispersion by a selective phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 24 publications
(35 reference statements)
1
64
0
Order By: Relevance
“…With 4 cm of MMF the output mode has a duration FWHM of 280 fs compared to 240 fs before the MMF, or a difference in second-order spectral phase of 2000 fs 2 (transform-limited FWHM 124 fs). A similar observation was also made in [11], by Morales-Delgado et al which demonstrated that if one employs a subset of MMF eigenmodes one can to a large extent retain the short pulse duration. The difference in our present work is that we can retain the short pulse duration while employing all MMF eigenmodes simultaneously, i.e.…”
Section: Optimal Trade-off Between Endoscope Length and Temporal Broasupporting
confidence: 72%
See 1 more Smart Citation
“…With 4 cm of MMF the output mode has a duration FWHM of 280 fs compared to 240 fs before the MMF, or a difference in second-order spectral phase of 2000 fs 2 (transform-limited FWHM 124 fs). A similar observation was also made in [11], by Morales-Delgado et al which demonstrated that if one employs a subset of MMF eigenmodes one can to a large extent retain the short pulse duration. The difference in our present work is that we can retain the short pulse duration while employing all MMF eigenmodes simultaneously, i.e.…”
Section: Optimal Trade-off Between Endoscope Length and Temporal Broasupporting
confidence: 72%
“…The so-called lensless endoscopes which have recently been demonstrated [5,6,7,8,9] might have the potential to overcome this challenge, since they are able to utilize standard multi-mode fiber (MMF) as probes which consequently have diameters down to 100 µm, and which might in principle be used as insertable needle-like imaging probes. However, achieving two-photon contrast in a lensless endoscope is a challenge due to dispersion in optical fibers, and only sparse reports of a two-photon lensless endoscopes exist [10,11]. Here, we draw upon concepts from light control in complex media [12,13,14,15,16] in order to propose an amalgam of the rigid endoscope and the lensless endoscope compatible with two-photon imaging which is, in effect, an ultra-thin rigid endoscope consisting of a short piece of graded-index MMF.…”
Section: Introductionmentioning
confidence: 99%
“…We note that this optimization is not applicable to the approach utilizing a single multimode optical fiber [e.g. 9, 10], for which the spread in group indices for the different modes makes the transmission and focusing of ultrashort optical pulses more challengingalthough we note that a small subset of modes with similar optical path lengths can be selected for short pulse transmission [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Optimization techniques [13][14][15] iteratively find the output pattern associated with each image from a predetermined set of inputs. In digital optical phase conjugation [16][17][18] such output patterns are recorded with a holographic acquisition. The transmission matrix method [19][20][21][22][23] captures the propagation characteristics of the fiber in a matrix linking the input field with the output field.…”
Section: Multimode Fiber Imagingmentioning
confidence: 99%
“…The scanning rate is currently in the kilohertz range in fastest implementations [19,21,24], yielding an effective frame rate of about 1Hz for highresolution scans. Most implementations to date were based on narrowband lasers, but extension to broadband pulsed lasers is underway [15,18].…”
Section: Multimode Fiber Imagingmentioning
confidence: 99%